Effects of locally produced bacterial phytase on humoral immunity, live body weight and blood characteristics in broilers vaccinated against Newcastle disease - Islam, R.; Ideris, Aini; Kasim, Azhar; Omar, Abdul Rahman; Meor Hussin, Anis Shobirin; Farhana Yasmin,; Akter, Yeasmin (Veterinary Association Malaysia, 2014)
Immune responses in association with body weight performance and hemato-biochemical constituents might influence the Newcastle disease (ND) vaccination by dietary phytase supplementation (Enterobacter sakazakii ASUA273). The objective of the study was to determine the effects of bacterial phytase supplementation on humoral immunity in association with live body weight and blood characteristics of broilers. Male-day-old Cobb broilers (n=180) were assigned into four phytase treatments (0, 500, 1000 and 1500 FTU/kg-1 of diet) with 12 cages comprised of 3 replicates and each cage contained 15 birds. Birds were maintained on formulated basal diet based with available phosphorus (0.19%) that lasted up to six weeks in feed. Birds were vaccinated with a live ND vaccine at day-old and 21 day-old. Two birds were randomly selected from each treatment weekly. Specific antibody to ND, non-specific immunoglobins (IgM, IgG, and IgA) and live body weight were measured weekly. At the end of experiment, the complete haemato-biochemical constituents were determined. Data of humoral immunity with live body weight and haemato- biochemical values were analysed based on factorial arrangement (treatments×weeks) of completely randomized design (CRD), respectively. Response of the humoral immunity shown that although serum-antibody of ND, IgM, and IgG levels were not improved, the mucosal IgA contents were increased with the increasing phytase doses. The live body weights of broilers were significantly increased (P<0.05) to the graded levels of phytase supplementation throughout the experimental period. Cumulative effects of mucosal IgA contents and live body weights of broilers showed significant (P<0.05) interaction between the effects of phytase levels and effects of weeks. Overall, phytase dose at 1500 FTU/kg-1 of diet over the age of 6 weeks-old showed the best performance. Conversely, no significant, sequential, and consistent treatment effects were observed on hemato-biochemical constituents in broiler chickens. It is therefore, concluded that the efficacy of this local phytase was flourished in respective to mucosal IgA contents and live body weights of broilers.